The political economics of civic energy: A framework for comparative research - Berka AL; Hoicka C; Sperling K (Elsevier B.V., 2025)
Deep civic engagement in energy transitions has been limited and unique to specific political economic contexts. This study develops a generic policy mix enabling civic energy, drawing on a systematic overview of barriers and policies for civic energy by country and region from 1980 to 2023. We show that when policy mixes support widespread diffusion of civic energy, they are likely to be “thick”; meaning that they align a wide range of corporate legal, market access, energy subsidy, localised planning and facilitation, access to finance, and capacity building policies - extending well beyond the domain of energy policy. Literature suggests that “thick” policy mixes emerge in contexts where there are narratives and conscious strategies for participation, political opportunities and resources mobilised towards enabling participation, with high degrees of fiscal and legislative decentralisation and policy coordination. In contrast, contexts characterised by low levels of civic energy are posited as having “thin” policy mixes, with limited opportunity for inclusive visioning or experimentation in multi-stakeholder platforms, limited decentralisation and policy coordination, resulting in marginalisation of civic arenas, conflicting framings and lack of high-level strategies for civic participation. We identify countries characterised by thick and thin policy mixes based on literature and identify research needed to confirm the existence of exclusive and inclusive governance and policy settings in relation to key indicators for both inclusivity and speed of transitions, allowing for better articulation of the value of inclusive innovation as a practical and beneficial approach to meeting emission reduction goals.
Keywords: Climate change; Energy communities; Energy democracy; Governance; Social innovation; Transition pathways